Investigating Algerian EFL Students’ Online Learning Readiness - Ammar Benabed; Amina Abdelhadi (Journal La Edusci, 2021)
Readiness is a critical factor to implement effective educational change. Accordingly, the present study aims to examine Algerian university EFL students’ online learning readiness. To reach this aim, a survey is conducted with 150 first year EFL students from Ibn Khaldoun University of Tiaret using an online questionnaire. The findings of this study highlight the correlation between EFL students’ readiness and willingness to online learning. It is found that due to technological constraints, the majority of EFL students demonstrate low level of online learning readiness which, in turn, affects their willingness to engage actively in this process. They rate themselves lower in terms of prior experience of online learning, time management, self directed learning, self efficacy, online communication and motivation. Hence, this study ends up with some suggestions and further practical implications.